Analisis Perhitungan Kebutuhan Tenaga Farmasi dengan Metode Workload Indicator Staffing Needs (WISN) di Puskesmas Imogiri I - Wulan Anindita Sari (Universitas Ahmad Dahlan, 2019)
Human resources are important assets that must be owned by a health service organization / institution. One of human resources is pharmacy. The number of pharmacy staff at Puskesmas Imogiri I is three people. Patient satisfaction in the Imogiri I Puskesmas pharmacy unit for the type of speed service in conducting low drug services is 73.00%. The number of patient visits served in the pharmaceutical unit is 100 patients / day, this pharmaceutical HR is known to have multiple duties in performing services. The Imogiri I Health Center has done an online workload analysis calculation using the Health Workforce Planning (Renbukt) application from the Ministry of Health of the Republic of Indonesia. The purpose of this study is to analyze the calculation of the needs of pharmaceutical workers using the Workload Indicator Staffing Needs (WISN) method at the Puskesmas Imogiri I. This study uses qualitative research with a research design that is the phenomenology approach. The subject of interviews and observations in this study amounted to 4 people. The data collection instrument used observation sheets and interview guides as well as in calculating the needs of pharmaceutical workers in the Imogiri I Puskesmas using the Workload Indicator Staffing Needs (WISN) method. The available work time for pharmacy workers at the Imogiri I Health Center in 1 year is 312 days or 1911 hours / year. The highest standard workload based on calculations is on receipt of prescriptions, making copies of prescriptions and delivery of drugs that is equal to 57330 minutes / year. The allowance standard for pharmaceutical workers is 0.11. The number of pharmacy needs is 2 people. Based on WISN calculations, there is a shortage of pharmacy workers, which is as much as 2 people from the number at the time of the study, which was as many as 3 people. So it is necessary to hold an additional amount of energy.